2017
DOI: 10.1038/ismej.2016.199
|View full text |Cite
|
Sign up to set email alerts
|

On the ecosystemic network of saliva in healthy young adults

Abstract: A dysbiotic state is believed to be a key factor in the onset of oral disease. Although oral diseases have been studied for decades, our understanding of oral health, the boundaries of a healthy oral ecosystem and ecological shift toward dysbiosis is still limited. Here, we present the ecobiological heterogeneity of the salivary ecosystem and relations between the salivary microbiome, salivary metabolome and host-related biochemical salivary parameters in 268 healthy adults after overnight fasting. Gender-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
130
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(145 citation statements)
references
References 53 publications
(58 reference statements)
9
130
0
Order By: Relevance
“…had fewer teeth with dental caries, were non-smokers, and other such factors) and had a lower risk for pneumonia-related death [20,26], suggesting that the predominance of N. flavescens, F. periodonticum , and P. pasteri is an indicator of healthy oral microbiota. Furthermore, a recent report by Zaura et al suggested that a bacterial community type characterized by a predominance of N. flavescens and Neisseria subflava positioned away from dysbiosis [27]. However, it is unexpected that a salivary microbiota predominant with Neisseria species is beneficial for health despite their capacity for high ACH production ability.…”
Section: Discussionmentioning
confidence: 99%
“…had fewer teeth with dental caries, were non-smokers, and other such factors) and had a lower risk for pneumonia-related death [20,26], suggesting that the predominance of N. flavescens, F. periodonticum , and P. pasteri is an indicator of healthy oral microbiota. Furthermore, a recent report by Zaura et al suggested that a bacterial community type characterized by a predominance of N. flavescens and Neisseria subflava positioned away from dysbiosis [27]. However, it is unexpected that a salivary microbiota predominant with Neisseria species is beneficial for health despite their capacity for high ACH production ability.…”
Section: Discussionmentioning
confidence: 99%
“…An elegant example of such an approach was recently published in a study showing that analysis of S. mutans in saliva based on adhesion subtypes could be used for future caries risk prediction [92]. It is also interesting that in a recent cross-sectional study from 2017 data showed that orally healthy individuals can be divided into five ecotypes based on characteristics of SM, the salivary metabolome and host-related biochemical salivary parameters [93]. In addition, a recent longitudinal study in hospitalized cancer patients demonstrated that increased variability of SM was associated with adverse clinical outcomes [94].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…At present, very few studies have studied saliva using both sequencing and metabolomics technologies. The most comprehensive study of this type has made steps in elucidating the relationships between salivary metabolites and associated microbial species [145]. There is a clear need for future work to reconcile the functional information provided by metabolomics with the oral microbial composition and host factors that may modify the latter.…”
Section: Future Directions For Salivary Metabolomicsmentioning
confidence: 99%